ВЗАЄМОДІЯ ВИКЛАДАЧА ТА СТУДЕНТІВ У ПРОЦЕСІ ЗАСТОСУВАННЯ ДИДАКТИЧНИХ ІГОР (Pedagogy of Higher and Secondary Education, 2012)
У статті висвітлено особливості взаємодії викладача та студентів у процесі застосування дидактичних ігор майбутніми вчителями у ВНЗ. Автор доводить, що використання ігрових методів збагачує професійну компетенцію випускника.Ключові слова: дидактичні ігри, майбутні вчителі, взаємодія викладача та студентів.The article is devoted to the problem of co-operation of teacher and students in the process of usage of didactic games by the future teachers in high schools. In the article the components of co-operation of teacher and students in the process of teaching are determined, in particular motivation, personality, organizational.Key words: didactic games, future teachers, co-operation of teacher and students.
Keywords: didactic games; future teachers; co-operation of teacher and students